2019
DOI: 10.1002/ijgo.12770
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional fetal biometry versus three‐dimensional fractional thigh volume for ultrasonographic prediction of birthweight

Abstract: Objective To develop and validate birthweight prediction models using fetal fractional thigh volume (TVol) in an Indian population, comparing them with existing prediction models developed for other ethnicities. Methods A prospective observational study was conducted among 131 pregnant women (>36 weeks) attending a tertiary hospital in New Delhi, India, for prenatal care between December 1, 2014, and November 1, 2016. Participants were randomly divided into formulating (n=100) and validation (n=31) groups. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In most previous studies, the primary limitation of using 3D ultrasound to measure fetal limb volume was to manually trace the limb boundaries of the ve cross-sections [10][11][12][13]15], which is time consuming and leads to limited clinical application. The 5D limb vol software in this study uses computer-aided measurement technology, which can automatically trace the boundary of the limb in cross-sections to obtain fetal limb volume and estimated fetal weight, and manual adjustment can be conducted if needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most previous studies, the primary limitation of using 3D ultrasound to measure fetal limb volume was to manually trace the limb boundaries of the ve cross-sections [10][11][12][13]15], which is time consuming and leads to limited clinical application. The 5D limb vol software in this study uses computer-aided measurement technology, which can automatically trace the boundary of the limb in cross-sections to obtain fetal limb volume and estimated fetal weight, and manual adjustment can be conducted if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that fractional limb volume combined with other 2D biological indicators can improve the precision of fetal weight estimation [11][12][13][14][15]. The recently launched automated software tool (5D Limb Vol) can automatically measure the fractional limb volume of the fetus approximately ve times faster than manual tracing [16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of 3D technology has been increasing in recent years. Sharma et al [25] compared the estimation of fetal weights measured both by 2D and 3D technologies and observed that the 3D method was more accurate. Becsek et al [26] reported a more accurate measurement of CRL by 3D technique when compared to the 2D approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the higher range of birth weight (greater than 4000 g), Both methods have similar accuracy (23). Correlation between CEFW and ABW (r = 0.074) was insignificant and was almost showed no relationship while a significant correlation between UEFW and ABW (r = 0.782) (5). But another study reported that the correlation coefficient for the CEFW was 0.78 and UEFW was 0.74 and it was statistically demonstrated that both showed significant positive correlation (p<0.001) (6).…”
Section: Figure 2: Correlation Between Cefwand Abw Figure 3: Correlatiomentioning
confidence: 99%